1982
DOI: 10.1111/j.1151-2916.1982.tb10387.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Parameters of Native Disorder in α‐Al2O3

Abstract: Compensation of single‐crystal, acceptor‐dominated samples of α‐Al2O3 by hydrogen leads to samples showing conductivity by protons, electrons, holes, Al‴i, and V‴Al Values of the partial conductivities as a function of temperature are used to determine the parameters of native ionic and electronic disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The relatively high variability of defect energies is attributed to the different interatomic potentials and computational methods used in the theoretical approaches. These relatively high formation energies will result in a small population of defects and the comparable formation energies make it difficult to determine the dominant oxygen vacancy formation mechanism [10]. Oxygen vacancies may also be formed as charge-compensating defects when aliovalent dopants are present -though this is beyond the scope of the present paper, which looks at undoped alumina only.…”
Section: Introductionmentioning
confidence: 73%
“…The relatively high variability of defect energies is attributed to the different interatomic potentials and computational methods used in the theoretical approaches. These relatively high formation energies will result in a small population of defects and the comparable formation energies make it difficult to determine the dominant oxygen vacancy formation mechanism [10]. Oxygen vacancies may also be formed as charge-compensating defects when aliovalent dopants are present -though this is beyond the scope of the present paper, which looks at undoped alumina only.…”
Section: Introductionmentioning
confidence: 73%
“…[9][10][11][12][13][14][15][16][17][18][19][20]30] found that yttrium acts as a donor for alumina. As yttrium is isoelectronic with aluminium, this effect is attributed to its large size (~ twice that of aluminium ions: 0.092 and 0.054 nm, respectively).…”
Section: As the Average Concentrations In The Polycrystal Cb And C~b mentioning
confidence: 99%
“…In many cases attempts have been made to compare the effect of yttrium on growth of the alumina scale with the effect of yttrium on the transport properties of massive aluminas which has been the object of many studies [9][10][11][12][13][14][15][16][17][18][19]. In the case of conductivity or diffusion experiments, all authors agree that yttrium incorporated in alumina as a doping element acts as a "donor".…”
Section: Introductionmentioning
confidence: 99%
“…The processes occurring at the oxide grain boundary may be due to physical blocking, complex defect formation or the action of yttrium as an iso-electronic donor. It has been suggested [38] that yttrium may act as an iso-electronic donor in Al2O3. It has also been proposed [39] that yttrium can act as an iso-electronic donor in C r z 0 3 , leading to a decrease in the concentration of chromium interstitials.…”
Section: Alteration In the Number And Character Of Short-circuit Diffmentioning
confidence: 99%